A.A.G.C. Jonker. Health decline and well-being in old age: the need of coping - Kempen, Gertrudis I. J. M.; Jonker, Angele (Tijdschrift voor Gerontologie en Geriatrie, 2011)
bespreking proefschriftA.A.G.C. Jonker. Health decline andwell-being in old age: the need of coping.